'Being and doing' in a new academic environment : challenges faced by seven Chinese post-graduate students at a South African University. - Shen, Chunyan (My University, 2009)
This research explores a range of academic and socio-cultural challenges faced by seven Chinese post-graduate students at the University of the Witwatersrand. The main aims of this study are to identify and understand any academic discourse challenges these students have been experiencing, together with any challenges in their new socio-cultural environment, such as financial or social challenges, and then to investigate the impact of these challenges on their studies and their identities as students. The study is based on data gathered from in-depth, semi-structured interviews with seven Chinese post-graduate students, from location ‘maps’ completed by each student and from some examples of the writing of three of the students. The findings suggest that these Chinese students are encountering great challenges in relation to English language proficiency and adjustments to new Discourses (Gee, 1996) – both academic and social. The data provide evidence that although these students feel socially disempowered in many respects, their attitudes toward academic study remain positive and each is making steady progress in his or her progamme of study and research. This finding indicates that there seems to be no explicit connection between positive social experiences and academic achievement and contrasts with findings from other research studies in which there is a correlation iii between positive or negative socio-cultural experiences and success or failure in the academy.
Keywords: Chinese post-graduates; New academic environment; Challenges